STRUKTUR CERITA DAN NILAI KEPAHLAWANAN DALAM CERITA RAKYAT DI KABUPATEN KARANGANYAR SEBAGAI MATERI AJAR DI SEKOLAH MENENGAH PERTAMA - Dita Puspitasari; Andayani Andayani; Sri Hastuti (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
The aims of this research are to describe the intrinsic structure of folklore, the heroism value of folklore, and relevance as literary teaching materials in junior high school. This research used qualitative description method with content analysis approach. The data sources are folklore texts, places and cultural heritage, and informants. Folklore used in this research are Asal Mula Nama Karanganyar, Perjuangan Raden Mas Said, and Joko Songo. Selected as the sample using purposive sampling and snowball sampling. The technique of data collection are documents analysis and interview. The data validity technique used are source and method triangulation. The technique of data analysis using interactive model of analysis that includes data collection, data reduction, data display, and conclusion drawing/verification. The result of this research are, (1) the structure contained in folklore in Karanganyar includes themes, characters, plot, setting, and message, (2) found 15 heroism value in folklore in Karanganyar District, (3) the folklore in Karanganyar is relevance with teaching materials in the junior high school.